The Influence of Social Media Marketing, Store Atmosphere, and Electronic Word of Mouth on Purchasing Decisions at Cafe Koat Kopi - Rachmawati, Putri Agustina; Harsoyo, Titik Desi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The goal of this study is to explore how Social Media Marketing, Store Atmosphere, plus Electronic Word of Mouth (E-WOM) influence consumer purchasing decisions at Café Koat Kopi. The study involved a sample of 100 respondents who had previously made purchases at the café. Data was gathered through a survey, utilizing a questionnaire as the primary research instrument. The findings of the study demonstrate that: (1) Social Media Marketing does not significantly influence purchasing decisions for products at Café Koat Kopi, (2) Store Atmosphere significantly and positively influences purchasing decisions, and (3) Electronic Word of Mouth (E-WOM) also plays a noteworthy and positively role in influencing purchasing decisions for Café Koat Kopi products.